THE EFFECTIVENESS OF ONLINE EDUCATION IN DEVELOPING WRITING SKILLS - Karimberganova Shahnoza Muxammad qizi,; Ruzmetova Diana Kamilovna, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
This paper discusses how online education contributes to enhancing the writing skills of second language learners. With the rapid development of digital technologies, writing instruction has gradually moved from the traditional classroom-based approach to virtual learning environments. This article focuses on the advantages, limitations, theoretical backgrounds, technological tools, feedback mechanisms, and psychological factors  that  influence  the  process  of  online  writing  development.  The  findings  of research  suggest  that  online  education  may  lead  to  significant  improvement  in  the writing proficiency of learners if it is supported by structured feedback, collaborative tasks,  and  digital  literacy.  However,  its  pace  might  be  hampered  by  limitations including reduced teacher presence, loss of motivation, and some technical issues. This paper concludes that online education works very effectively when supported by sound instructional design.